Analysis of the liver functional reserve of patients with advanced hepatocellular carcinoma undergoing sorafenib treatment: Prospects for regorafenib therapy. Issue 12 (22nd June 2018) - Terashima, Takeshi; Yamashita, Tatsuya; Sunagozaka, Hajime; Arai, Kuniaki; Kawaguchi, Kazunori; Kitamura, Kazuya; Yamashita, Taro; Sakai, Yoshio; Mizukoshi, Eishiro; Honda, Masao; Kaneko, Shuichi
Abstract : Aim: This study aimed to investigate liver functional reserves during sorafenib treatment for advanced hepatocellular carcinoma (HCC), to identify predictive factors for maintaining them, and to analyze the proportion of candidates for regorafenib, which has been proven to improve patients' outcomes in the RESORCE trial. Methods: We retrospectively investigated Child–Pugh scores during and after sorafenib treatment and evaluated their effects on second‐line treatment and outcomes of 125 patients with advanced HCC. Results: Pretreatment Child–Pugh A was maintained in 59/90 (65.6%) patients and pretreatment Child–Pugh B was improved to Child–Pugh A in 10/35 (28.6%) patients when sorafenib ceased. A Child–Pugh score = 5 and aspartate amino transferase <40 IU/L before treatment were contributing factors; vascular invasion and cessation of sorafenib due to gastrointestinal or liver‐related adverse effects were reverse predictive factors for Child–Pugh A when sorafenib treatment ceased. Significantly more patients with Child–Pugh A when sorafenib treatment ceased received subsequent therapy and achieved better outcomes compared with patients with Child–Pugh B. When sorafenib treatment failed, 45/125 patients (36.0%) fulfilled key inclusion criteria of the RESORCE trial as follows: Child–Pugh A, Eastern Cooperative Oncology Group performance status 0 or 1, tumor progression revealed by imaging, and treatment with ≥400 mg sorafenib for at least 20 of the last 28 days before treatment failure in 56.8%, 84.8%, 73.6%, and 68.0% of patients, respectively. Conclusions: A comprehensive understanding and management of dynamic changes in liver functional reserve during sorafenib treatment contributed to the efficacy of subsequent therapy (e.g. regorafenib) and to better outcomes for patients with advanced HCC.